Mobile app to play team-building games - Liao, Qian Ping (2019)
In recent decades, corporate organisations are leaning towards establishing a team-oriented work structure and culture. These organisations have also realised that poor communication between employees in the team can lead to undesired failures and unproductive performance, affecting the organisations financially. In efforts to promote bonding between employees, many organisations engage trainers to conduct team-building workshops, where participants carry out physical collaborative activities with common goals to achieve intended results. After the activities, employees build more positive interpersonal relationships with each other, effectively boosting employee engagement to the organisations. The emergence of virtual workplaces around the world poses challenges to organisations, as their employees are unable to participate in physical team-building activities without coming together in the same place. This project aims to develop a team-building mobile game application for teams of people located in different physical spaces to perform simple collaborative tasks digitally, thus enhancing teamwork and trust towards each other. This project documents the design and implementation of the game application Break The Ice. Break The Ice features a puzzle game with rotating puzzle pieces, and players in the team must rotate the puzzle pieces back to their original orientation to complete the game. Players are connected globally with a multiplayer networking service with the matchmaking function, supporting the flexibility to form their own teams.